Impact of Rock Phosphate Levels, Placement Methods, and Cowpea Varieties on Yield Parameters in Sokoto - Sokoto, Aliyu Lawal; Yarima, Usman Abdullahi (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Cowpea is a vital crop in arid and semi-arid regions of Nigeria, contributing significantly to food security. However, its yield is often limited by phosphorus deficiency. This study investigates the effects of varying rock phosphate levels, placement methods, and cowpea varieties on yield parameters in Sokoto during the 2024 cropping season. The experiment involved two cowpea varieties (Sampea-7 and Baadare), three rock phosphate levels (25, 50, and 75 kg ha−1), and three placement methods (plough-sole, broadcast, and side-band). Results showed significant responses to rock phosphate application and placement methods on grain yield, pod weight, and shelling percentage. The study highlights the importance of optimizing rock phosphate application strategies to enhance cowpea yield in phosphorus-deficient soils.